Method Development and Validation of Simultaneous Estimation of Pseudoephedrine Ambroxol Desloratadine in Tablet Dosage Form and Degradation Studies By Rp-Hplc Method - Dr.K.Sujana, Mohammad Mubina (International Journal of Scientific Research and Management (IJSRM), 2017)
A simple, Accurate, precise method was developed for the simultaneous estimation of the Pseudoephedrine, Ambroxol and Desloratadine in Tablet dosage form. Chromatogram was run through ODS 250mm x 4.6 mm, 5m. Mobile phase containing Buffer, Acetonitrie and Methanol in the ratio of 50:20A:30M was pumped through column at a flow rate of 1ml/min. Buffer used in this method was 0.01N KH2PO4 buffer at pH 3.2. Temperature was maintained at 30°C. Optimized wavelength for Pseudoephedrine and Ambroxol was 225nm. Retention time of Pseudoephedrine, Ambroxol and Desloratadine were found to be 2.417min, 4.518min and 7.464min respectively. %RSD of the Pseudoephedrine, Ambroxol and Desloratadine were and found to be 1.03 0.64 and 1.15respectively. %Recover was Obtained as 99.92%, 100.21% and 99.92% for Pseudoephedrine, Ambroxol and Desloratadine respectively. LOD, LOQ values are obtained from regression equations of Pseudoephedrine(0.01ppm, 0.02ppm), Ambroxol(0.15ppm, 1.44ppm) and Desloratadine(0.06ppm, 0.17ppm). Regression equation of Pseudoephedrine is y = 16947x + 319.2 Ambroxol is y = 19401x + 3236.and Desloratidine y = 38993x +2051.